Correction to: a normative reference vs. Baseline testing compromise for ImPACT: the CARE consortium multiple variable prediction (CARE-MVP) norms - Asken, B. M.; Houck, Z. M.; Schmidt, J. D.; Bauer, R. M.; Broglio, S. P.; McCrea, M. A.; McAllister, T. W.; Clugston, J. R. (Sports Medicine, 2020)
Unfortunately, in the published article the symbol "%ile" has incorrectly been published as "‰". We have now corrected this in all the occurrences.